Cytotoxicity and genotoxicity of natural resin-based experimental endodontic sealers - Silva, Gleyce O. [UNESP]; Cavalcanti, Bruno N. [UNESP]; Oliveira, Tatiana R. [UNESP]; Bin, Claudia V. [UNESP]; Camargo, Samira E. A. [UNESP]; Camargo, Carlos H. R. [UNESP] (Springer Nature, 2016)
Objectives: The development of endodontic sealers based on natural resins seems to be promising, given their improved biological properties. This study evaluated the cytotoxic and genotoxic effects of two experimental root canal sealers, based on extracts from Copaifera multijuga and Ricinus communis (castor oil polymer), comparing them to synthetic resin-based sealers: a single methacrylate-based, a multi-methacrylate-based, and an epoxy resin-based sealers. Materials and methods: Sealers were prepared, set, and exposed to cell culture medium for 24 h at 37 °C with CO2. V79 cells were exposed to serial dilutions of the extracts of each sealer for 24 h. Cell viability was measured by the MTT assay and genotoxicity was assessed by the formation of micronuclei. Results: The single methacrylate-based sealer had the most cytotoxic effects, with significant reduction in cell viability in all dilutions of the extract. The castor oil polymer-based sealer was, on the other hand, the most biocompatible sealer, with no cytotoxic effects at any concentration. All tested sealers were not genotoxic, excepting the single methacrylate-based sealer. Conclusions: The tested natural resin-based sealers presented low cytotoxic and no genotoxic effects on cell cultures. Clinical relevance: These results may suggest a good alternative to develop new endodontic sealers, in order to achieve better biological response and healing, when compared to commercially available sealers.
Keywords: Biocompatibility; Cytotoxicity; Genotoxicity; Root canal sealer